Anti-seepage and anti-crack cement-based mortar and preparation method thereof
By using silicate cement and fast hard sulfaluminate cement in cement-based mortar, combining materials such as desulfurization gypsum, vitrified microbeads and polypropylene fibers, an efficient anti-seepage and crack-resistant cement-based mortar was solved. The problem of cement-based mortar is prone to cracking and lack of anti-seepage insulation, which achieves mortar with high early strength and late strength, significantly improving the durability and safety of concrete.
Patent Information
- Application Number
- CN202411256783.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing cement-based mortars are prone to cracking in engineering applications and lack anti-seepage and insulation properties, resulting in insufficient durability and service life of concrete structures, posing safety hazards.
A cement-based mortar with anti-seepage and crack resistance is adopted, and its raw materials include silicate cement, fast hard sulfaluminate cement, desulfurization gypsum, vitrified microbeads, expanded perlite, acrylate emulsion, polypropylene fiber and mortar reinforcement , through specific mixing and treatment methods, insulation mortar with high early strength and late strength is formed, enhancing compressive strength and anti-seepage performance.
It significantly improves the compressive strength, anti-seepage effect and thermal insulation performance of the mortar, extends the service life of the concrete structure, reduces safety hazards, and is convenient to construct and is suitable for large-scale promotion.
Smart Images

Figure CN119118608A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building mortar, and in particular to an anti-seepage and crack-resistant cement-based mortar and a preparation method thereof. Background Art
[0002] At present, cracks and damages are inevitable in wall concrete during engineering applications, which not only seriously affects the normal use of concrete structures, but also brings great safety hazards and economic losses. During the service life of concrete structures, if cracks cannot be repaired in time, external water and corrosive media will continue to penetrate through the surface defects of the material, which will cause the accelerated deterioration of concrete durability.
[0003] In order to solve the problem of concrete cracking, external insulation materials and other means are generally used. External insulation materials are generally organic materials, which have poor integrity with the original concrete and low durability. Cement-based mortar refers to a mortar mixed with cement, aggregate, water, and lime and additives added as needed. The wall concrete protective layer is mostly ordinary cement-based mortar, which is not only easy to crack, but also lacks anti-seepage and thermal insulation properties. The existing thermal insulation mortar has a large internal porosity, relatively low mortar strength, and poor durability. Although it can be doped with organic materials, it will cause obvious deficiencies in mechanical properties. At the same time, the anti-cracking and anti-seepage properties cannot meet the requirements, and there are safety hazards.
[0004] How to solve the problem of anti-seepage and anti-cracking of cement-based mortar, ensure its thermal insulation performance, and improve the durability and service life of concrete structures is of great practical significance. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an anti-seepage and anti-cracking cement-based mortar and a preparation method thereof.
[0006] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include, by mass, 55-80 parts of cement, 35-50 parts of fly ash, 10-20 parts of desulfurized gypsum, 10-20 parts of vitrified microspheres, 14-20 parts of expanded perlite, 2-5 parts of acrylic ester emulsion, 2-6 parts of mortar reinforcing agent, 1-3 parts of polypropylene fiber, 1.5-3.2 parts of acrylic acid, 0.4-1 parts of air entraining agent, 0.1-1 parts of calcium formate, 1-2 parts of water reducing agent and 120-180 parts of water.
[0007] The mortar enhancer is prepared by the following steps: lactide, decanolactone and glycerol are mixed, stirred at 140-150°C under nitrogen protection until melted, a catalyst is added and stirred for 10-20 hours, cooled to room temperature, added to toluene, diphenylmethane diisocyanate is added under nitrogen protection and stirred for 1-2 hours, amino-terminated polyamide amine is added and stirred for 5-10 hours, cooled to room temperature, centrifuged, washed and vacuum dried.
[0008] Cement includes: Portland cement and rapid-hardening sulphoaluminate cement.
[0009] Preferably, the silicate cement is PO42.5 silicate cement.
[0010] Preferably, the fast-hardening sulphoaluminate cement is PO42.5 fast-hardening sulphoaluminate cement.
[0011] Preferably, the mass ratio of silicate cement to rapid hardening sulphoaluminate cement is 40-50:5-15.
[0012] Preferably, the fly ash is Class II fly ash, with a loss on ignition ≤8%, a fineness ≤20%, and an activity index 28d ≥70%.
[0013] Preferably, the solid content of the acrylic ester emulsion is 45-65%.
[0014] Preferably, the water reducing agent is a polycarboxylic acid-based water reducing agent.
[0015] Preferably, the polypropylene fibers have a length of 3-19 mm and a diameter of 0.2-0.5 mm.
[0016] Preferably, in the mortar enhancer, the mass ratio of lactide, decanolactone, glycerol, catalyst, diphenylmethane diisocyanate, and amino-terminated polyamidoamine is 1-3: 1-4: 0.01-0.1: 0.01-0.1: 1-2: 5-10.
[0017] Preferably, in the mortar strengthener, the catalyst is stannous octoate.
[0018] Preferably, in the mortar enhancer, the generation number of the amino-terminated polyamidoamine is 1.0-3.0 generations.
[0019] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0020] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 20-25 kV for 5-15 min, immersed in an acrylic acid solution, and irradiated with 254 nm ultraviolet light for 10-30 min. During the ultraviolet irradiation, the temperature is maintained at 30-50° C. to obtain activated polypropylene fiber;
[0021] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 1-5 minutes, then add air entraining agent, water reducing agent and calcium formate and continue stirring for 10-30 seconds.
[0022] Preferably, the mass fraction of the acrylic acid solution is 10-16%.
[0023] Beneficial effects:
[0024] The present invention adopts silicate cement and fast-hardening sulphoaluminate cement as the compound, which not only produces very high early strength after hardening, but also the desulfurized gypsum can react with the fast-hardening sulphoaluminate cement to promote the expansion of the early hardened body, which not only helps to enhance the anti-seepage effect, but also improves the density of the matrix, which improves the thermal insulation performance on the one hand and is conducive to the growth of later strength on the other hand.
[0025] The present invention grafts acrylic acid on the surface of the activated polypropylene fiber, which can enhance the compatibility and interface bonding force between the polypropylene fiber and the matrix, and is beneficial to maintaining the good dispersion state of the polypropylene fiber in the matrix; and can also have extremely high affinity with the acrylic ester emulsion and undergo a certain degree of polymerization to form a network structure in the matrix, which can move and deform together with the matrix under the action of tensile stress, thereby greatly enhancing the compressive strength of the thermal insulation mortar layer.
[0026] Through experiments, it was found that when the mass ratio of polypropylene fiber, acrylic acid, acrylic emulsion and gelling material is 1-3:1.5-3.2:2-5:100-150, the compressive strength and anti-seepage effect of the thermal insulation mortar layer are the best; if the amount of polypropylene fiber or acrylic acid decreases, the compressive strength of the thermal insulation mortar layer will decrease accordingly; if the amount of polypropylene fiber or acrylic acid is too high, the uniformity of the dispersion of activated polypropylene fiber in the matrix will begin to deteriorate, causing excessive concentration of local stress when subjected to force, resulting in a significant decrease in compressive strength, and poor anti-seepage effect and durability.
[0027] Since the amino-terminated polyamide amine has a dendritic structure and contains a large number of active amino groups at the end, the present invention combines a multi-arm polymer at the end of its dendritic structure, which can not only fully stretch in the cement mortar matrix and interact with each other, but its multi-arm structure can effectively promote the uniform dispersion of vitrified microspheres and expanded perlite in the system, and the two work together to form a good skeleton structure, which is conducive to the increase of the compressive strength of the later curing. At the same time, the molecular chain of the mortar enhancer has excellent flexibility, can be matched with acrylic emulsion, and can gradually lose water during the slurry hardening process, which can not only improve the flexibility of the mortar and increase the fluidity of the slurry, but also can form an interpenetrating network structure with cement and aggregate (vitrified microspheres and expanded perlite) during the cement hydration process, playing a role similar to toughening fiber, not only effectively preventing the cracking of cement products, but also having the functions of dense filling and anti-shrinkage, and excellent thermal insulation performance.
[0028] The cement-based mortar of the present invention is reasonably designed, easy to operate, has the characteristics of high early strength and stable later strength development, has high thermal insulation strength and excellent anti-seepage and anti-cracking properties, improves the flexibility of the mortar, significantly improves the fluidity of the mortar, is easy to construct, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1The figures are a comparison of the fluidity of the anti-seepage and anti-cracking cement-based mortars obtained in Example 5 and Comparative Examples 1-3, and a comparison of the dry density of the samples obtained in Example 5 and Comparative Examples 1-3.
[0030] Figure 2 It is a comparison chart of the compressive strength and thermal conductivity of the samples obtained in Example 5 and Comparative Examples 1-3.
[0031] Figure 3 It is a comparison chart of the linear shrinkage and softening coefficient of the samples obtained in Example 5 and Comparative Examples 1-3.
[0032] Figure 4 It is a comparison chart of chloride ion permeability coefficients of the samples obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0033] The present invention will be further explained below in conjunction with specific embodiments.
[0034] The PO42.5 silicate cement used below was purchased from Anhui Mouluo Cement Co., Ltd. The PO42.5 fast-hardening sulphoaluminate cement used below was purchased from Zhengzhou Moudense Material Co., Ltd. The Class II fly ash used below was purchased from Hebei Moushun Mining Co., Ltd. The acrylic emulsion used below was purchased from Shandong Mouquan New Material Technology Co., Ltd., and its solid content is 55%. The polycarboxylic acid water reducer and air entraining agent used below were purchased from Nanjing Mouyi Synthetic Technology Co., Ltd., the polycarboxylic acid water reducer model is CP1701X, and the air entraining agent model is AE360. The polypropylene fiber used below was purchased from Shandong Mouhe New Material Co., Ltd., with a length of 3-19 mm and a diameter of 0.2-0.5 mm.
[0035] The particle size distribution of vitrified microspheres and expanded perlite is as follows:
[0036]
[0037] Example 1
[0038] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 5500g of PO42.5 silicate cement, 3500g of Class II fly ash, 1000g of desulfurized gypsum, 1000g of vitrified microspheres, 1400g of expanded perlite, 200g of acrylate emulsion, 200g of mortar enhancer, 100g of polypropylene fiber, 150g of acrylic acid, 40g of air entraining agent, 10g of calcium formate, 100g of polycarboxylic acid water reducer, and 12000g of water.
[0039] The mortar enhancer was prepared by the following steps: 100 g of lactide, 100 g of decanolactone and 1 g of glycerol were mixed, and stirred at 140°C until melted under nitrogen protection, 1 g of stannous octoate was added and stirred for 10 h, cooled to room temperature, added to 2000 g of toluene, 100 g of diphenylmethane diisocyanate was added and stirred for 1 h under nitrogen protection, 500 g of 1.0 generation amino-terminated polyamidoamine was added and stirred for 5 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0040] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0041] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 20 kV for 5 min, immersed in a 10% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 10 min. During the ultraviolet irradiation, the temperature is maintained at 30° C. to obtain activated polypropylene fiber;
[0042] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 1 min. Then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 10 s.
[0043] Example 2
[0044] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 8000g of cement, 5000g of Class II fly ash, 2000g of desulfurized gypsum, 2000g of vitrified microspheres, 2000g of expanded perlite, 500g of acrylate emulsion, 600g of mortar strengthener, 300g of polypropylene fiber, 320g of acrylic acid, 100g of air entraining agent, 100g of calcium formate, 200g of polycarboxylic acid water reducer, and 18000g of water.
[0045] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 8:1.
[0046] The mortar enhancer was prepared by the following steps: 300 g of lactide, 400 g of decanolactone and 10 g of glycerol were mixed, and stirred at 150°C until melted under nitrogen protection, 10 g of stannous octoate was added and stirred for 20 h, cooled to room temperature, added to 4000 g of toluene, 200 g of diphenylmethane diisocyanate was added and stirred for 2 h under nitrogen protection, 1000 g of 3.0 generation amino-terminated polyamidoamine was added and stirred for 10 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0047] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0048] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 25 kV for 15 min, immersed in a 16% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 30 min. During the ultraviolet irradiation, the temperature is maintained at 50° C. to obtain activated polypropylene fiber;
[0049] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 5 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 30 seconds.
[0050] Example 3
[0051] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 6500g of cement, 4500g of Class II fly ash, 1300g of desulfurized gypsum, 1800g of vitrified microspheres, 1700g of expanded perlite, 400g of acrylate emulsion, 300g of mortar strengthener, 250g of polypropylene fiber, 230g of acrylic acid, 80g of air entraining agent, 30g of calcium formate, 170g of polycarboxylic acid water reducer, and 14000g of water.
[0052] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 10:3.
[0053] The mortar enhancer was prepared by the following steps: 250 g of lactide, 200 g of decanolactone and 7 g of glycerol were mixed, and stirred at 142°C until melted under nitrogen protection, 7 g of stannous octoate was added and stirred for 12 h, cooled to room temperature, added to 3500 g of toluene, 130 g of diphenylmethane diisocyanate was added and stirred for 100 min under nitrogen protection, 700 g of 2.0 generation amino-terminated polyamidoamine was added and stirred for 9 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0054] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0055] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 22 kV for 12 min, immersed in a 12% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 25 min. During the ultraviolet irradiation, the temperature is maintained at 35° C. to obtain activated polypropylene fiber;
[0056] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 4 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 15 seconds.
[0057] Example 4
[0058] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 7000g of cement, 4000g of Class II fly ash, 1700g of desulfurized gypsum, 1200g of vitrified microspheres, 1900g of expanded perlite, 300g of acrylate emulsion, 500g of mortar strengthener, 150g of polypropylene fiber, 260g of acrylic acid, 60g of air entraining agent, 70g of calcium formate, 130g of polycarboxylic acid water reducer, and 16000g of water.
[0059] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 7:2.
[0060] The mortar enhancer was prepared by the following steps: 150 g of lactide, 300 g of decanolactone and 3 g of glycerol were mixed, and stirred at 148°C until melted under nitrogen protection, 3 g of stannous octoate was added and stirred for 18 h, cooled to room temperature, added to 2500 g of toluene, 170 g of diphenylmethane diisocyanate was added and stirred for 80 min under nitrogen protection, 900 g of 2.0 generation amino-terminated polyamidoamine was added and stirred for 7 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0061] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0062] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 24 kV for 8 minutes, immersed in a 14% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 15 minutes. During the ultraviolet irradiation, the temperature is maintained at 45° C. to obtain activated polypropylene fiber;
[0063] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 2 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 25 seconds.
[0064] Example 5
[0065] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 6800g of cement, 4200g of Class II fly ash, 1500g of desulfurized gypsum, 1500g of vitrified microspheres, 1500g of expanded perlite, 350g of acrylate emulsion, 400g of mortar strengthener, 200g of polypropylene fiber, 240g of acrylic acid, 70g of air entraining agent, 50g of calcium formate, 150g of polycarboxylic acid water reducer, and 15000g of water.
[0066] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 9:2.
[0067] The mortar enhancer was prepared by the following steps: 200 g of lactide, 250 g of decanolactone and 5 g of glycerol were mixed, and stirred at 145°C until melted under nitrogen protection, 5 g of stannous octoate was added and stirred for 15 h, cooled to room temperature, added to 3000 g of toluene, 150 g of diphenylmethane diisocyanate was added and stirred for 90 min under nitrogen protection, 800 g of 2.0 generation amino-terminated polyamidoamine was added and stirred for 8 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0068] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0069] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 23 kV for 10 min, immersed in a 13% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 20 min. During the ultraviolet irradiation, the temperature is maintained at 40° C. to obtain activated polypropylene fiber;
[0070] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 3 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 20 seconds.
[0071] Comparative Example 1
[0072] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 6800g of cement, 4200g of Class II fly ash, 1500g of desulfurized gypsum, 1500g of vitrified microspheres, 1500g of expanded perlite, 350g of acrylate emulsion, 400g of mortar strengthener, 200g of polypropylene fiber, 240g of acrylic acid, 70g of air entraining agent, 50g of calcium formate, 150g of polycarboxylic acid water reducer, and 15000g of water.
[0073] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 9:2.
[0074] The mortar enhancer was prepared by the following steps: 200 g of lactide, 250 g of decanolactone and 5 g of glycerol were mixed, and stirred at 145°C until melted under nitrogen protection, 5 g of stannous octoate was added and stirred for 15 h, cooled to room temperature, added to 3000 g of toluene, 150 g of diphenylmethane diisocyanate was added and stirred for 90 min under nitrogen protection, 800 g of 2.0 generation amino-terminated polyamidoamine was added and stirred for 8 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0075] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0076] S1. Soaking the polypropylene fiber in a 13% by mass acrylic acid solution, irradiating with 254 nm ultraviolet light for 20 min, maintaining the temperature at 40° C. during the ultraviolet irradiation process, to obtain activated polypropylene fiber;
[0077] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 3 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 20 seconds.
[0078] Comparative Example 2
[0079] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 6800g of cement, 4200g of Class II fly ash, 1500g of desulfurized gypsum, 1500g of vitrified microspheres, 1500g of expanded perlite, 350g of acrylate emulsion, 400g of mortar strengthener, 200g of polypropylene fiber, 240g of acrylic acid, 70g of air entraining agent, 50g of calcium formate, 150g of polycarboxylic acid water reducer, and 15000g of water.
[0080] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 9:2.
[0081] The mortar enhancer was prepared by the following steps: 200 g of lactide, 250 g of decanolactone and 5 g of glycerol were mixed, and stirred at 145°C until melted under nitrogen protection, 5 g of stannous octoate was added and stirred for 15 h, cooled to room temperature, added to 3000 g of toluene, 150 g of diphenylmethane diisocyanate was added and stirred for 90 min under nitrogen protection, 800 g of 2.0 generation amino-terminated polyamidoamine was added and stirred for 8 h, cooled to room temperature, centrifuged, washed and vacuum dried.
[0082] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0083] S1, feeding the polypropylene fiber into a glow discharge plasma generator, and treating the fiber with 23 kV discharge for 10 min to obtain activated polypropylene fiber;
[0084] S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 3 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 20 seconds.
[0085] Comparative Example 3
[0086] A seepage-proof and crack-resistant cement-based mortar, whose raw materials include: 6800g of cement, 4200g of Class II fly ash, 1500g of desulfurized gypsum, 1500g of vitrified microspheres, 1500g of expanded perlite, 350g of acrylic emulsion, 150g of methyl hydroxyethyl cellulose ether, 200g of polypropylene fiber, 240g of acrylic acid, 70g of air entraining agent, 50g of calcium formate, 150g of polycarboxylic acid water reducer, and 15000g of water.
[0087] The cement is obtained by mixing PO42.5 silicate cement and PO42.5 rapid hardening sulphoaluminate cement in a mass ratio of 9:2.
[0088] The preparation method of the above-mentioned anti-seepage and anti-cracking cement-based mortar comprises the following steps:
[0089] S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 23 kV for 10 min, immersed in a 13% by mass acrylic acid solution, and irradiated with 254 nm ultraviolet light for 20 min. During the ultraviolet irradiation, the temperature is maintained at 40° C. to obtain activated polypropylene fiber;
[0090] S2. Mix cement, desulfurized gypsum, fly ash, vitrified microspheres, methyl hydroxyethyl cellulose ether and expanded perlite evenly, then add acrylic emulsion, activated polypropylene fiber and water and stir for 3 minutes, then add air entraining agent, polycarboxylate water reducer and calcium formate and continue stirring for 20 seconds.
[0091] The anti-seepage and anti-cracking cement-based mortars obtained in Example 5 and Comparative Examples 1-3 were used for comparative experiments, as follows:
[0092] (1) With reference to GB / T 2419-2005 “Method for determination of fluidity of cement mortar”, a cement mortar fluidity tester was used to determine the fluidity of the anti-seepage and anti-cracking cement-based mortars obtained in Example 5 and Comparative Examples 1-3.
[0093] (2) The anti-seepage and anti-cracking cement-based mortar obtained in Example 5 and Comparative Examples 1-3 was cast into test pieces with a specification of 40 mm×40 mm×160 mm. After standard curing for 28 days, the dry density, compressive strength, thermal conductivity, linear shrinkage and softening coefficient of the samples obtained in Example 5 and Comparative Examples 1-3 were measured with reference to GB / T20473-2021 "Building Thermal Insulation Mortar"; and the chloride ion permeability coefficient of the samples obtained in Example 5 and Comparative Examples 1-3 was measured with reference to GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0094] like Figures 1 to 4As shown, there is no significant difference in the dry density of the thermal insulation mortar samples obtained in Example 5 and Comparative Examples 1-3 (P>0.05), but the thermal insulation mortar obtained in Example 5 has the highest fluidity, and the thermal insulation mortar sample obtained in Example 5 has the highest compressive strength and softening coefficient, while the thermal conductivity, linear shrinkage and chloride ion permeability coefficient are the lowest, which are better than Comparative Examples 1-3 (P<0.05).
[0095] The applicant believes that this is because the present invention uses silicate cement and fast-hardening sulphoaluminate cement to compound, which not only produces high early strength after hardening, but also desulfurized gypsum can react with fast-hardening sulphoaluminate cement to promote the expansion of the early hardening body, which not only helps to enhance the anti-seepage effect, but also improves the density of the matrix, on the one hand, improves the thermal insulation performance, and on the other hand, is conducive to the growth of later strength. The present invention grafts acrylic acid on the surface of the polypropylene fiber after activation, which can not only enhance the compatibility and interfacial bonding between the polypropylene fiber and the matrix, but also help to maintain the good dispersion state of the polypropylene fiber in the matrix; it can also have a very high affinity with the acrylic ester emulsion, and undergo a certain degree of polymerization, forming a network structure in the matrix, which can move and deform with the matrix under the action of tensile stress, so that the compressive strength of the thermal insulation mortar layer is greatly enhanced. At the same time, the present invention combines a multi-arm polymer at the end of the branch structure of the amino-terminated polyamide amine, which can not only fully stretch in the cement mortar matrix and interact with each other, but also its multi-arm structure can effectively promote the uniform dispersion of vitrified microspheres and expanded perlite in the system, and the two synergistically form a good skeleton structure, which is conducive to the growth of the later curing compressive strength. At the same time, the molecular chain of the mortar enhancer has excellent flexibility and can be combined with acrylic emulsion. It can gradually lose water during the hardening process of the slurry, which can not only improve the flexibility of the mortar and improve the fluidity of the slurry, but also form an interpenetrating network structure with cement and aggregate (vitrified microspheres and expanded perlite) during the cement hydration process, playing a role similar to toughening fiber. It not only effectively prevents the cracking of cement products, but also has the effect of dense filling and anti-shrinkage, and has excellent thermal insulation performance.
[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An anti-seepage and anti-cracking cement-based mortar, It is characterized in that The raw materials include, by mass: 55-80 parts of cement, 35-50 parts of fly ash, 10-20 parts of desulfurized gypsum, 10-20 parts of vitrified microspheres, 14-20 parts of expanded perlite, 2-5 parts of acrylic emulsion, 2-6 parts of mortar reinforcing agent, 1-3 parts of polypropylene fiber, 1.5-3.2 parts of acrylic acid, 0.4-1 parts of air entraining agent, 0.1-1 parts of calcium formate, 1-2 parts of water reducing agent, and 120-180 parts of water; The mortar enhancer is prepared by the following steps: lactide, decanolactone and glycerol are mixed, stirred at 140-150°C under nitrogen protection until melted, a catalyst is added and stirred for 10-20 hours, cooled to room temperature, added to toluene, diphenylmethane diisocyanate is added under nitrogen protection and stirred for 1-2 hours, amino-terminated polyamide amine is added and stirred for 5-10 hours, cooled to room temperature, centrifuged, washed and vacuum dried.
2. According to the anti-seepage and anti-cracking cement-based mortar of claim 1, It is characterized in that Cement includes: Portland cement, rapid hardening sulphoaluminate cement; The silicate cement is PO42.5 silicate cement; The fast-hardening sulphoaluminate cement is PO42.5 fast-hardening sulphoaluminate cement; The mass ratio of silicate cement to rapid hardening sulphoaluminate cement is 40-50:5-15.
3. According to the anti-seepage and anti-cracking cement-based mortar of claim 1, It is characterized in that The fly ash is Class II fly ash, with loss on ignition ≤8%, fineness ≤20%, and activity index 28d ≥70%.
4. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that The solid content of acrylic emulsion is 45-65%.
5. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that The water reducing agent is a polycarboxylic acid water reducing agent.
6. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that The length of polypropylene fibers is 3-19 mm and the diameter is 0.2-0.5 mm.
7. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that In the mortar enhancer, the mass ratio of lactide, decanolactone, glycerol, catalyst, diphenylmethane diisocyanate and amino-terminated polyamide amine is 1-3:1-4:0.01-0.1:0.01-0.1:1-2:5-10.
8. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that In the mortar enhancer, the catalyst is stannous octoate.
9. The anti-seepage and anti-cracking cement-based mortar according to claim 1, It is characterized in that In the mortar enhancer, the generation of the amino-terminated polyamidoamine is 1.0-3.0 generations.
10. A method for preparing the anti-seepage and anti-cracking cement-based mortar according to any one of claims 1 to 9, It is characterized in that The steps include: S1. The polypropylene fiber is fed into a glow discharge plasma generator, discharged at 20-25 kV for 5-15 min, immersed in an acrylic acid solution, and irradiated with 254 nm ultraviolet light for 10-30 min. During the ultraviolet irradiation, the temperature is maintained at 30-50° C. to obtain activated polypropylene fiber; S2. Evenly mix cement, desulfurized gypsum, fly ash, vitrified microspheres, mortar enhancer and expanded perlite, then add acrylic emulsion, activated polypropylene fiber and water and stir for 1-5 minutes, then add air entraining agent, water reducing agent and calcium formate and continue stirring for 10-30 seconds.
Citation Information
Patent Citations
Acrylic ester emulsion modified cement base rapid repair mortar
CN102211919A
Preparation method and use of multi-arm polymer-grafted silica
CN106866991A
Compression-resistant hollowing-free thermal insulation mortar
CN111620625A
Anti-mud polycarboxylic acid water reducing agent and preparation method thereof
CN112126021A
